Penanganan dan Pengaturan Container Pada PT. Terminal Peti Kemas (TPK) Pelindo Belawan (Jurnal Manajemen Kreatif dan Inovasi, 2023)
The purpose of this paper is to find out how "Container Handling and Arrangement at PT. Terminal Peti Kemas (TPK) Pelindo Belawan. The purpose of this study is to explore various aspects of Container Handling and Arrangement at PT. Terminal Peti Kemas (TPK) Pelindo Belawan in the context of the modern logistics industry. This study will discuss the latest methods and technologies used in container management, as well as their impact on operational efficiency and cost reduction. Container handling and arrangement are important components in international trade, so they require careful planning and implementation. By investing in new equipment, implementing automation technology, developing efficient logistics systems, and providing training and development programs, ports can improve efficiency and effectiveness in container handling and arrangement. The data used in this study are primary data obtained through field research, direct interviews with the company and secondary data obtained from books and journals in the library (library research) or other reading sources related to the subject matter taken.